2014
DOI: 10.1016/j.crad.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study evaluating catheter-directed contrast-enhanced ultrasound compared to catheter-directed computed tomography arteriography as adjuncts to digital subtraction angiography to guide transarterial chemoembolization

Abstract: CCEUS is a potentially valuable imaging tool in adjunction to DSA when performing TACE and may provide similar information to CCTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…A few centers have employed direct intra-arterial administration of microbubble contrast agents (intra-arterial CEUS) during transarterial liver tumor interventions such as TACE to assess tumor vascular supply. Burgmans et al (57) performed a pilot study in which they performed intra-arterial CEUS along with digital subtraction angiography from the proper hepatic, segmental, and subsegmental arterial positions during TACE. They found that intra-arterial CEUS changed the treatment plan in almost half of patients, whether by identifying additional tumor feeding vessels or resulting in a change in catheter position, with results similar to those provided by catheter-directed CT hepatic angiography.…”
Section: Intra-arterial Ceus During Tacementioning
confidence: 99%
“…A few centers have employed direct intra-arterial administration of microbubble contrast agents (intra-arterial CEUS) during transarterial liver tumor interventions such as TACE to assess tumor vascular supply. Burgmans et al (57) performed a pilot study in which they performed intra-arterial CEUS along with digital subtraction angiography from the proper hepatic, segmental, and subsegmental arterial positions during TACE. They found that intra-arterial CEUS changed the treatment plan in almost half of patients, whether by identifying additional tumor feeding vessels or resulting in a change in catheter position, with results similar to those provided by catheter-directed CT hepatic angiography.…”
Section: Intra-arterial Ceus During Tacementioning
confidence: 99%
“…Information similar to that provided by IAUS may be acquired using CTA and cone-beam CT. Oblique acquisition may also be performed to define the positional relationship of the tumor on DSA, but the procedure is complicated and time-consuming, and increases the exposure dose and contrast medium volume, all of which are disadvantageous[ 15 , 30 ]. Also, renal function is decreased in many patients with hepatic cirrhosis, and worsens with iodine contrast medium.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, when nonenhancing areas are located anteriorly or posteriorly, they are not appreciable with two-dimensional angiography. Burgmans et al [57] proposed injecting microbubbles under US guidance directly through the intraarterial catheter in order to have a multiplanar visualization before TACE. A modification in the treatment approach occurred in 44.4% of cases due to the additional information provided by this technique, which was consistent with catheter-directed CT arteriography, used as a reference for intrahepatic findings.…”
Section: Guidance and Evaluation Of Hcc Treatmentsmentioning
confidence: 99%